Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) untuk Mencegah Scabies pada Remaja di Pondok Pesantren As’ad Jambi - Kurnia, fitriyan; Putri, Satiti Kawuri (Jurnal Abdimas Kesehatan (JAK), 2025)
Environmentally and behavior-based infectious diseases, such as skin diseases, continue to be a significant health issue in Islamic boarding schools. Scabies is a contagious skin infection caused by the Sarcoptes scabiei mite, commonly found in tropical countries. Generally, crowded environments such as Islamic boarding schools are at high risk for the transmission of this disease. The objective of this activity was to provide knowledge on Clean and Healthy Living Behavior (PHBS) to students  at Pondok Pesantren As’ad in order to prevent scabies. The activity was conducted using a lecture method, followed by pre-test and post-test assessments before and after the session. The activities were carried out from March to August 2024 at As’ad boarding schools in Jambi City, with 27 students in attendance. The material was delivered using PowerPoint presentations. The results indicated that, prior to the education, the students' knowledge about PHBS to prevent scabies was still considered poor, with 21 students (77.77%) having inadequate knowledge. After the education, the students' knowledge improved to a good level, with 20 students (74.07%) demonstrating better understanding. This improvement was evident in the increase of the average pre-test score from 51.48 to 73.33 on the post-test. Based on these results, it can be concluded that the students' knowledge increased after receiving education on PHBS for preventing scabies. It is expected that the management of the boarding schools will further enhance promotive and preventive activities emphasizing the importance of Clean and Healthy Living Behavior, especially in the prevention of scabies.